Multi-stage delivery nano-particle systems for therapeutic applications - Serda, Rita E.; Godin, Biana; Blanco, Elvin; Chiappini, Ciro; Ferrari, Mauro (Biochimica et biophysica acta, 2011)
The daunting task for drug molecules to reach pathological lesions has fueled rapid advances in Nanomedicine. The progressive evolution of nanovectors has led to the development of multi-stage delivery systems aimed at overcoming the numerous obstacles encountered by nanovectors on their journey to the target site. This review summarizes major findings with respect to silicon-based drug delivery vectors for cancer therapeutics and imaging. Based on rational design, well-established silicon technologies have been adapted for the fabrication of nanovectors with specific shapes, sizes, and porosities. These vectors are part of a multi-stage delivery system that contains multiple nano-components, each designed to achieve a specific task with the common goal of site-directed delivery of therapeutics. Quasi-hemispherical and discoidal silicon microparticles are superior to spherical particles with respect to margination in the blood, with particles of different shapes and sizes having unique distributions in vivo. Cellular adhesion and internalization of silicon microparticles is influenced by microparticle shape and surface charge, with the latter dictating binding of serum opsonins. Based on in vitro cell studies, the internalization of porous silicon microparticles by endothelial cells and macrophages is compatible with cellular morphology, intracellular trafficking, mitosis, cell cycle progression, cytokine release, and cell viability. In vivo studies support superior therapeutic efficacy of liposomal encapsulated siRNA when delivered in multi-stage systems compared to free nanoparticles. This article is part of a Special Issue entitled Nanotechnologies - Emerging Applications in Biomedicine.